# 1973 USAMO Problems/Problem 2

(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)

## Problem

Let $\{X_n\}$ and $\{Y_n\}$ denote two sequences of integers defined as follows:

$X_0=1$, $X_1=1$, $X_{n+1}=X_n+2X_{n-1}$ $(n=1,2,3,\dots),$
$Y_0=1$, $Y_1=7$, $Y_{n+1}=2Y_n+3Y_{n-1}$ $(n=1,2,3,\dots)$.

Thus, the first few terms of the sequences are:

$X:1, 1, 3, 5, 11, 21, \dots$,
$Y:1, 7, 17, 55, 161, 487, \dots$.

Prove that, except for the "1", there is no term which occurs in both sequences.

## Solution

We can look at each sequence $\bmod{8}$:

$X$: $1$, $1$, $3$, $5$, $3$, $5$, $\dots$,
$Y$: $1$, $7$, $1$, $7$, $1$, $7$, $\dots$.
• Proof that $X$ repeats $\bmod{8}$:

The third and fourth terms are $3$ and $5$ $\bmod{8}$. Plugging into the formula, we see that the next term is $11\equiv 3\bmod{8}$, and plugging $5$ and $3$, we get that the next term is $13\equiv 5\bmod{8}$. Thus the sequence $X$ repeats, and the pattern is $3,5,3,5,\dots$.

• Proof that $Y$ repeats $\bmod{8}$:

The first and second terms are $1$ and $7$ $\bmod{8}$. Plugging into the formula, we see that the next term is $17\equiv 1\bmod{8}$, and plugging $7$ and $1$, we get that the next term is $23\equiv 7\bmod{8}$. Thus the sequence $Y$ repeats, and the pattern is $1,7,1,7,\dots$.

Combining both results, we see that $X_i$ and $Y_j$ are not congruent $\bmod{8}$ when $i\geq 3$ and $j\geq 2$. Thus after the "1", the terms of each sequence are not equal.

## Solution 2

We can solve this problem by finding a particular solution for each linear recurrence.

$X_{n+1} - X_n - 2X_{n-1} = 0$ with characteristic polynomial

$X^2 - X - 2 = (X - 2)(X + 1)$, so $X = -1, 2$

$X_n = A(2)^n + B(-1)^n$

After plugging in to find the particular solution:

$X_0 = 1 = A + B$

$X_1 = 1 = 2A - B$

$A = \frac{1}{3}$ and $B = \frac{2}{3}$, so

$X_n = \frac{1}{3}(2)^n + \frac{2}{3}(-1)^n$

Doing the same for $Y_n$, we get

$Y_n = 2(3)^n - (-1)^n$

We know they're equal at $n = 0$, so let's set them equal and compare.

$2(3)^n - (-1)^n = \frac{1}{3}((2)^n + 2(-1)^n)$

$6(3)^n - 3(-1)^n = (2)^n + 2(-1)^n$

$6(3)^n - 2^n = 5(-1)^n$

By induction, we know in general that $(\alpha + 1)^n > \alpha^n$ for all $\alpha, n > 0$, so $6(3)^n > 2^n$ for all $n > 1$.

Therefore, the left hand side is always increasing and will never equal 5 again, so equality between $X_n$ and $Y_n$ only holds when $n = 0$, so they only share 1 term.